Compilation of commercial property price indices for Germany tailored for policy use - Thomas A. Knetsch (Deutsche Bundesbank, 2020)
The compilation of commercial property price indices is a big challenge. In Germany, substantive data gaps prevent the calculation of official figures by the national statistical authority. By contrast, policymakers urge for timely, reliable and comprehensive data. In this paper, proposals are made as to how to aggregate and classify individual price information in order to best serve the intended policy uses. Experimental price indices according to various definitions of commercial real estate are constructed on the basis of two components: (i) the appraisals for transaction prices of houses, apartments, multi-family dwellings, office buildings and retail space in 127 German towns and cities provided by bulwiengesa, a real estate consulting company; and (ii) corresponding data on floor space which make it possible to derive coherent weighting schemes. The overall price developments revealed by the various indices are rather similar in terms of central time series characteristics, while differences in detail can be explained by their specific compositions. Analysts may find these indices helpful to better understand price developments in German commercial real estate markets. Statisticians may acquire from this exercise further knowledge about measurement practices, as official statistics are encouraged to take steps towards establishing thorough reporting on commercial real estate markets.
Keywords: C43; E31; R33; 330; Commercial property price indices; private data; stock weighting; policy use